ISLAM MENGUNGKAP DEMOKRASI (PRESPEKTIF SEJARAH DI MASA NABI DAN KHULAFA’ AL-RASYIDIN) - Hani'atul Khoiroh (MIYAH : Jurnal Studi Islam, 2021)
Abstract: Nowadays, it may be difficult for a government that does not implement itself with a democratic system, because democracy is a political system that occupies the top stratum accepted by many countries. However, democracy differs in different countries, depending on how the country provides broad rights and obligations to its people in terms of government. Because of this, this article aims to explain how Islam itself reveals about real democracy, and how the reality of democracy was during the time of the prophet and Khulafa'al-Rasyidin. Al-Qur'an al-Karim does not clearly express the word democracy, but the Qur'an has provided principles as the foundation of democracy which is then implemented in the world of government. The principles of democracy have been stated among them are: QS. al-Shura: 38 and QS. Ali Imran: 159 (about deliberation), QS. an-Nahl: 90, QS. al-Maidah: 8 and QS. al-Shura: 15 (about justice), QS. al-Hujurat: 13 (about equality), QS. an-Nisa ': 58 (about trust), QS. Ali Imran: 104 (on freedom of criticism), QS. al-Nisa': 59, 83 and QS. al-Syuro: 38 (on freedom of opinion). There is no doubt that the concept of democracy has existed in the Qur'an which is indeed a reference for the people of all time. Not only that, the real life of a democratic society has also been realized by the Prophet Muhammad and Khulafa'al-Rasyidin as an ideal country, an example for a state that is thayyibah wa rabbun ghafur..Kata Kunci: Islam, Democracy, Historical Perspective.